Structuring Mental Health Discourse: A Genre-Based Analysis of Ted Talks - Raudatul Hasanah; Reli Handayani; Armiwati (CV. Eureka Murakabi Abadi, 2026)
Public speaking is one of human communication manifestations, in which presenters impart knowledge while simultaneously inspiring and influencing their audience. The well-known public speaking platform TED Talk is renowned for its captivating delivery that blends charisma, persuasiveness, and clarity. Previous studies on TED Talks have focused on the persuasive strategies, while this study highlights recurrent structural patterns employed in TED Talks using Swales’ Genre Analysis framework. Although several studies have used Swales' theory of speech structure, no study has fully utilized this framework in examining TED Talks, particularly on the topic of mental health. A subject that has recently attracted a lot of public interest. Four TED Talk transcripts with the highest viewers were analyzed using a qualitative descriptive method and Swales' Genre Analysis theory to determine the rhetorical